International Survey on the Management of Wake-Up Stroke - Luís Henrique de Castro-Afonso (Cerebrovascular Diseases Extra, 2016)
Background: Patients who wake up having experienced a stroke while asleep represent around 20% of acute stroke admissions. According to international guidelines for the management of acute stroke, patients presenting with wake-up stroke are not currently eligible to receive revascularization treatments. In this study, we aimed to assess the opinions of stroke experts about the management of patients with wake-up stroke by using an international multicenter electronic survey. Method: This study consisted of 8 questions on wake-up stroke treatment. Results: Two hundred invitations to participate in the survey were sent by e-mail. Fifty-nine participants started the survey, 4 dropped out before completing it, and 55 completed the full questionnaire. We had 55 participants from 22 countries. Conclusions: In this study, most stroke experts recommended a recanalization treatment for wake-up stroke. However, there was considerable disagreement among experts regarding the best brain imaging method and the best recanalization treatment. The results of ongoing randomized trials on wake-up stroke are urgently needed.